Combustion Based Synthesis of AlN Nanoparticles Using a Solid Nitrogen Promotion Reaction. Issue 12 (23rd September 2015) - Nersisyan, Hayk H.; Yoo, Bung Uk; Lee, Tae Hyuk; Lee, Jong Hyeon
Abstract : Combustion based synthesis of AlN nanoparticles using the "solid nitrogen" promotion reaction was investigated in Al2 O3 + 3Mg system in nitrogen atmosphere. A controlled amount of Mg + 0.5NH4 Cl mixture as a solid source of nitrogen was blended with the Al2 O3 + 3Mg starting system and the synthesis reaction of AlN nanoparticles was conducted using the exothermic heat of the entire reaction system. The resulting AlN nanoparticles were characterized by X‐ray diffraction (XRD), Raman and Fourier transform infrared spectroscopy (FTIR), PL spectroscopy, field‐emission scanning electron microscopy, transmission electron microscopy, and Brunauer–Emmett–Teller surface area techniques. The analysis results confirmed that single phase and crystalline AlN nanoparticles with an average size of 50–500 nm were obtained from the developed approach. Photoluminescence spectra of AlN nanopowders under the excitation of 230–270 nm UV light revealed that AlN emits yellow‐red light having a wavelength near to 590 nm. The chemistry of the combustion process is discussed and the basic reactions that led to the formation of AlN are presented.